Evaluation of rice (Oryza sativa)- based cropping sequences under rainfed medium land situation of Bihar plateau - BANIK, P; SARKAR, B; SASMAL, T; GHOSAL, P K; ADHIKARY, S; BAGCHI, D K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1992-95 to evaluate the production potential and economics of different rice (Oryza sativa L.) - based cropping sequences on rainfed, medium land of eastern plateau. Three rice cultivars, viz ’MW 10’, ’Pusa Jaldi Dhan 5’ and ’RR 167-982’ were followed by 4 winter crops, viz toria [Brassica rapa (L.) Thell emend. Metzger var napus L., syn B. campestris L. spp oleifera (Metzger) Sinsk var loria], niger (Guizatia abyssinica Coss.), horsegram (Macrotyloma uniflorum Lam.) and linseed (Linum usitatissimum L.) in a split-plot design. ’RR 167-982’ rice gave the maximum grain yield (1.44 tonnes/ha). Among the different sequences ’RR 167-982’ rice-linseed recorded the maximum rice equivalent yield of 3.27 tonnes/ha followed by ’RR 167-982’ rice-toria. ’MW 10’ rice-linseed gave the highest land-use efficiency value (61.09%), whereas the highest production efficiency was recorded in ’RR 167-982’ rice-toria (15.39 kg/ha/day). Thus ’RR 167-982’ rice-linseed sequence may be recommended for this area as it gave the maximum gross returns (Rs 9 606/ha) and net return (Rs 5 516/ha).